Obecność Spółdzielni Wydawniczej „Czytelnik” w Łodzi (styczeń–lipiec 1945) - Rzadkowolska, Magdalena (Acta Universitatis Lodziensis. Folia Librorum, 2014)
After the end of World War II Łódź was an important center of Polish cultural life. The city housed the editorial offices of newspapers, publishers, writers lived here. For half a year, Łódź was the seat of the most important post–war publisher, Publishing Cooperative „Czytelnik”. The purpose was to provide the President Borejsza’s writers only good conditions for creative work. Publishing activity was concentrated in Warszawa. 69